Prevalence and control of ketosis in postparturient holstein cows in selected regions of Iran - Samiei, Abdollah (2011)
This thesis investigated the prevalence of ketosis among 1,002 Iranian Holstein cows in 13 regions in Iran and examined the relationship between concentrations of β-hydroxybutyrate (BHBA) in milk and blood to assess the reliability of the BHBA concentrations in milk measured by a semi quantitative keto-test paper to detect subclinical ketosis (SCK). In addition, the relationships between dietary energy level, body condition score (BCS) and butyric silage with SCK in dairy cows during first month after calving and the effect of supplementation of Glycol-Line (a commercial glucose precursor) plus non-fiber carbohydrate (NFC) in diet on BHBA and glucose concentrations, based on the reduction of prevalence of SCK in fresh cows (four weeks after calving) were studied. The prevalence of SCK and clinical ketosis among cows in the 13 regions were 12.21% and 3.52%, respectively. The mean milk production for cows suffering from clinical ketosis, SCK and healthy cows were 28, 35 and 45 kg/d, respectively, suggesting a reduction in milk yield for the diseased cows. There were associations between regions, lactation stage, blood glucose and peak milk yield during first month lactating (p<0.01). The correlation between blood glucose concentration and lactation stage was also significant (p<0.01). High correlation coefficients were observed between blood BHBA and blood NEFA, and between blood and milk BHBA. Milk yield of cattle with SCK decreased (p<0.01) but fat percentage and milk fat:protein ratio increased (p<0.01) as compared to those of the health cows. The commercial keto-test paper used had a low false positive result at a cut-off point of 200 μmol of BHBA/L of milk. The results showed that the best time to assess SCK using the commercial keto-test paper was 0, 14 and 17 days after calving. Although in the total mixed ration (TMR), net energy for lactation (NEL, 1.48 Mcal/kg), crude protein (CP, 13.4%) and NFC (30.5%) were lower while the fibre (NDF 44.23%) were higher than the recommended requirements of lactating cows, only NEL was found to be significantly (p<0.05) affecting incidence of SCK. Butyric acid concentration in the corn silage was high in four out of the ten farms studied but butyric acid had no significant effect on the occurrence SCK. Cows showed more than 0.5 unit loss of BCS during first month after calving because of the low energy content of the TMR used in the farms. However, BCS at calving was normal in most of the dairy cows and had no significant effect on the incidence of SCK. Blood BHBA concentration was lower in cows fed with 38% NFC (non-fiber carbohydrate) and 300 g Glyco-Line in the close-up period and 40% NFC and 300 g Glyco-Line during the first month after calving (513 μmol/L). They also had higher blood glucose concentration than the other groups. Average milk yield was the highest when 300 g Glycol-Line and 40% NFC were fed (37.5 kg/cow/d). Therefore, the most effective way to control or minimize incidence of SCK in dairy farms under conditions similar to those in this study would be to provide sufficient dietary energy to meet the requirements of the cows, especially during the first month after calving when the SCK prevalence is normally high.